Pengembangan Perikanan Tangkap Berbasis Sumberdaya Ikan Demersal Di Perairan Kota Dumai Provinsi Riau - Isnaniah ' (Universitas Riau, 2010)
Develop fishing with regard to the code of conduct for responsible fisheries (CCRF) as suggested by the FAO. The objectives of the research were: 1) analysisstatus of fish resources utilization in Dumai, and 2) analysis fishing technology thatis good to be developed in Dumai (biology,social and techno-economic). Thisreseach was focused on fishing gears i.e. Bottom long line, Scoopnet, Portable trap.Result of research indicated that exploiting of fish resourcees demersal in territorialwater Dumai over Total Allowable Catches (TAC) 80% from MSY. Sondong isfishing gear of main priority of development with regard to CCRFKeywords: Development, by Demersal Resources, TAC